Injectable Gelatin Hydrogel Suppresses Inflammation and Enhances Functional Recovery in a Mouse Model of Intracerebral Hemorrhage - Xu, Jiake; Duan, Zhongxin; Qi, Xin; Ou, Yi; Guo, Xi; Zi, Liu; Wei, Yang; Liu, Hao; Ma, Lu; Li, Hao; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
Intracerebral hemorrhage (ICH) is a devastating subtype of stroke with high morbidity and mortality. However, there is no effective therapy method to improve its clinical outcomes to date. Here we report an injectable gelatin hydrogel that is capable of suppressing inflammation and enhancing functional recovery in a mouse model of ICH. Thiolated gelatin was synthesized by EDC chemistry and then the hydrogel was formed through Michael addition reaction between the thiolated gelatin and polyethylene glycol diacrylate. The hydrogel was characterized by scanning electron microscopy, porosity, rheology, and cytotoxicity before evaluating in a mouse model of ICH. The in vivo study showed that the hydrogel injection into the ICH lesion reduced the neuron loss, attenuated the neurological deficit post-operation, and decreased the activation of the microglia/macrophages and astrocytes. More importantly, the pro-inflammatory M1 microglia/macrophages polarization was suppressed while the anti-inflammatory M2 phenotype was promoted after the hydrogel injection. Besides, the hydrogel injection reduced the release of inflammatory cytokines (IL-1β and TNF-α). Moreover, integrin β1 was confirmed up-regulated around the lesion that is positively correlated with the M2 microglia/macrophages. The related mechanism was proposed and discussed. Taken together, the injectable gelatin hydrogel suppressed the inflammation which might contribute to enhance the functional recovery of the ICH mouse, making it a promising application in brain injury of CNS diseases.